A study of nominal inflection in Latin inscriptions : a morpho-syntactic analysis - Gaeng, Paul A. (North Carolina studies in the Romance languages and literatures, 1977)
Paul A. Gaeng's exhaustive morpho-syntactic analysis of Latin nominal declensions, as found in Christian funerary inscriptions from the Roman Empire, seeks to establish the extent to which this inscribed material reflects the period's linguistic evolution: from classical Latin's multi-case structure to the one-case system of Western Romance Languages. The study draws on E. Diehl's three-volume Inscriptiones Latinae Veteres and J.D. Vives's Inscripciones cristianas de las Espanas romana y visigoda for its heterogeneous dataset. Gaeng's work forms a valuable contribution to the study of the dissolution of the Latin declensional system in the shift from Latin to Romance.